Evaluation of Teaching Ability of Students at Japanese Language Education Program of FKIP UNRI - Rahayu, Nana (Proceedings of the UR International Conference on Educational Sciences, 2018)
This study aims to find out the factors of influencing the ability to teach Japanese in Japanese Language Education Program of Faculty of Teacherâs Training and Education of Universitas Riau (FKIP UNRI) students who carried out Teacher Training Program (PPL) at school. This research is a descriptive research where data was obtained through documentation. The population in this study was all students carrying out PPL during 2017/2018 school year totaling 50 people. Research data was collected through assessment documentation and video recording. The data is analyzed descriptively. Based on the results of the study it can be concluded that the factors that influence the ability to teach students are the role of supervising teachers, lack of preparation for teaching planning, and limited teaching materials.